SOCIAL EXCLUSION AS AN OBJECT OF ECONOMIC ANALYSIS - Z. Halushka; М. Soboljeva (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In the article essence and forms of display of social exception of separate citizens and certain layers of population are certain as the socioeconomic phenomenon. Theoretical principles and methodology of estimation of the phenomenon of social exception are analyzed. Certain characteristic lines of social exception: subzero even consumptions and profit of individuals or groups; a limit access is to the public mechanisms of increase of welfare; a mainly passive type of cooperating is with society. Attention is accented on a defect for the individuals of row of rights, limit nature of access to the institutes that distribute resources, to the labor-market. Poverty is certain the main category of social exception. A concept "circles of poverty" and mechanisms of its existence are reasonable. Other displays of social exception-direct violation of base human rights are examined on quality education, on medical services and kind health, on the acceptable standard of living, on access to cultural acquisition, on defense of the interests and on the whole on participating in economic, social, in a civilized manner, political life of country. Cited data about part of torn away housekeeping of Ukraine on separate signs. The analysis of distribution of housekeeping after the amount of the accumulated signs of the social tearing away gave an opportunity to set a limit after that the social tearing away begins brightly to show up, at the level of 5 signs. It is certain the limit of the sharp tearing away. The second degree of tearing away – critical – answers a presence 7thsigns. At this level in Ukraine there are 37,7. That's far more than those, who are considered poor on a relative national criterion (24,0). It is set that conception of social exception shows the "horizontal cut" of the system of social relations and place of individual, layer, group and others like that in this system, certain on certain signs. The necessity of the use of interdisciplinary approaches is well-proven in an order to find intercommunication of those factors that predetermine the problem of social exception, and set possibility of the practical use of these researches in development of principles of economic and social politics. Complex approach is offered for the study of this phenomenon with the aim of improvement of principles of economic and social politics of the state.